2017
DOI: 10.18535/jmscr/v5i4.207
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Immediate Outcome of Early Onset Neonatal Sepsis

Abstract: Background -Neonatal septicemia remains one of the main causes of mortality and morbidity despite the progress in hygiene, introduction of new and potent antimicrobial agents for treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This study was also supported by a study conducted in Iraq which reported that neonates with neonatal sepsis who were born from mothers having history of fever were more likely to die than neonates with neonatal sepsis who were born from mothers who had no history of fever (24). Our study was also in line with a study conducted in India which reported that intra partum fever was signi cant predictor of mortality related to neonatal sepsis (25). This might be because the fact that the diseasecausing agent of maternal infection can ascend to the baby via circulation and during passage through the birth canal.…”
Section: Discussionsupporting
confidence: 91%
“…This study was also supported by a study conducted in Iraq which reported that neonates with neonatal sepsis who were born from mothers having history of fever were more likely to die than neonates with neonatal sepsis who were born from mothers who had no history of fever (24). Our study was also in line with a study conducted in India which reported that intra partum fever was signi cant predictor of mortality related to neonatal sepsis (25). This might be because the fact that the diseasecausing agent of maternal infection can ascend to the baby via circulation and during passage through the birth canal.…”
Section: Discussionsupporting
confidence: 91%
“…Similar observations were recorded by Jajoo M et al, Bhutta et al, Jumah et al and many others. [7][8][9][10]12,13 Similarly, associate higher mortality rates in patients with thrombocytopenia, CRP positivity, leucopoenia and hyperglycaemia. Although non-specific for neonatal sepsis, CRP has the highest sensitivity, specificity and high negative and high positive predictive values.…”
Section: Discussionmentioning
confidence: 99%
“…n= (Z1-α/2) 2 × P (1-P) / d 2 Margin of error= 5% Z1-α/2 = Confidence level 95%=1.96 P = Expected proportion in population = 11.7% least among all [Rahul V Bharad et al] 6 d= absolute precision = 5% Informed and written consent was taken from the parents or guardian of the neonates. All neonates of both gender who were more than 30 weeks of gestation presenting to neonatal unit within 7 days of life fulfilling the definition of early onset sepsis as per operational definition were included and Patients who had received antibiotics before presentation and Patients not agreed to participate in study were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Prematurity was found in 71 (59.1%) patients and APGAR score <5 at 1 minute was found in 62 (51.7%) patients. [6,19] The purpose of this study is to find the maternal and neonatal contributing factors which are associated with increased risk of early onset of sepsis in neonates presenting to remotely situated tertiary care hospital in rural areas. Identification of risk factors will help us to predict the risk of early onset sepsis in neonates and will help us to start empiric treatment early and will decrease the mortality as well morbidity that is associated with neonatal sepsis.…”
Section: Introductionmentioning
confidence: 99%